Electrophysiological and structural determinants of electrotonic modulation of repolarization by the activation sequence - Walton, Richard D.; Benson, Alan; Hardy, Matthew; White, Ed; Bernus, Olivier (Frontiers in Physiology, 2013)
Spatial dispersion of repolarization is known to play an important role in arrhythmogenesis. Electrotonic modulation of repolarization by the activation sequence has been observed in some species and tissue preparations, but to varying extents. Our study sought to determine the mechanisms underlying species- and tissue-dependent electrotonic modulation of repolarization in ventricles. Epi-fluorescence optical imaging of whole rat hearts and pig left ventricular wedges were used to assess epicardial spatial activation and repolarization characteristics. Experiments were supported by computer simulations using realistic geometries. Tight coupling between activation times (AT) and action potential duration (APD) were observed in rat experiments but not in pig. Linear correlation analysis found slopes of -1.03±0.59 and -0.26±0.13 for rat and pig, respectively (p